German macro: How it's Different and Why that Matters - George Bratsiotis; David Cobham; Peter Bofinger; Michael Burda; Panicos O. Demetriades; Lars P. Feld; Brigitte Granville; Bernd Hayo; Florian Neumeier; Jacques Mélitz; Charles Wyplosz; Fabian Zuleeg (European Policy Centre (EPC), 2016)
The starting point of this project is the question of whether the macroeconomics of the German political establishment does indeed differ, as it often seems to do, from standard textbook macroeconomics: in particular, the former appears to neglect demand management (although it may be quite interventionist in other ways), to reject debt relief and to emphasise structural reform designed to improve competitiveness as the (only) key to economic growth. How far is this true? How much of whatever difference exists is due to a well worked out set of ideas in the form of Ordoliberalism? How does it relate to Germany's own experiences in different periods? How far is this the result of political preferences and how much do the idiosyncrasies of these German views matter, for the development of the Eurozone and indeed the health of the German economy?
Keywords: 330; Macroeconomic Policy; German political establishment; Eurozone